1998
DOI: 10.1103/physrevlett.80.5663
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dipole-Dipole Interaction between Elementary Radiators Near a Surface

Abstract: We report the results of elastic light-scattering measurements of random silver nanoparticle arrays fabricated onto structures supporting optical surface modes (i.e., surface plasmons or waveguide modes). We observe dramatic, qualitative changes in the resonance structure of the nanoparticle layer due to coupling with the propagating modes. The effect appears to arise because the underlying surface modes mediate an enhanced dipole-dipole interaction between individual nanoparticles. A calculation that supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
148
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 220 publications
(152 citation statements)
references
References 15 publications
2
148
1
1
Order By: Relevance
“…The enhancements in absorption and elastic scattering [64] are likely associated with the existence of strongly enhanced local fields. These changes are attributed to an enhancement of the dipoledipole interaction between the different particles mediated by propagating modes that are supported by a layered sample [64], interaction between dipole and its own image [62], and interference effects between waves reflected from different interfaces in the sample [63].…”
Section: Multi-layer Asf Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancements in absorption and elastic scattering [64] are likely associated with the existence of strongly enhanced local fields. These changes are attributed to an enhancement of the dipoledipole interaction between the different particles mediated by propagating modes that are supported by a layered sample [64], interaction between dipole and its own image [62], and interference effects between waves reflected from different interfaces in the sample [63].…”
Section: Multi-layer Asf Structuresmentioning
confidence: 99%
“…A metal nanostructured film positioned near a mirror-like metal surface with a sandwiched dielectric layer can show dramatic change in the film's optical properties [62][63][64]. The localized plasmon resonances supported by the constituents of metal island films experience a frequency shift when placed in close proximity to a conducting surface [62].…”
Section: Multi-layer Asf Structuresmentioning
confidence: 99%
“…Using metals in structures to mediate light transfer between di!erent media is only the tip of the iceberg, however; the resonances of metallic nanoparticles can be exploited further via their mutual interaction, an area of research that has hardly been explored and opens up an entirely new chapter in the way periodic structures can be used [134]. Another avenue is that of self-organised assembly, where the interaction between plasmon resonances on the surface of metallic nanoparticles can be used to aid the formation of periodic structures [135].…”
Section: Surface Plasmonsmentioning
confidence: 99%
“…Surface plasmons are usually associated with thin "lms, but they can also be observed in small metal spheres [131,132]. Recent work at the University of Rochester, USA, where resonances in small metal particles have been studied, has shown that the detection e$ciency of thin-"lm photodectors can be increased by over an order of magnitude (in a limited wavelength range) if the surface is covered with metal islands [133,134]. The explanation that the authors propose is that the incoming radiation couples to the metallic resonance and then to Fig.…”
Section: Surface Plasmonsmentioning
confidence: 99%
See 1 more Smart Citation